Grand challenge: addressing the global challenge of healthy aging - Browning, Colette; Ory, Marcia; Ahn, SangNam; Thomas, Shane (Frontiers in Public Health, 2025)
This article reflects upon contemporary issues for the study of healthy ageing and highlights several grand challenges for public health and ageing. Prepared by the Specialty Chief Editors, this Grand Challenge article calls for innovative, equity-focused research and practice to support healthy aging globally. Key research topics include reframing aging as an opportunity, addressing multimorbidity, emphasizing prevention across the life course, applying implementation science, incorporating economic evaluation, using up-to-date data and advanced analytic methods, and promoting inclusion of underrepresented populations.